2018
DOI: 10.1007/s00704-018-2438-0
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution dynamical downscaling of re-analysis data over the Kerguelen Islands using the WRF model

Abstract: We have used the Weather Research and Forecasting (WRF) model to simulate the climate of the Kerguelen Islands (49°S, 69°E) and investigate its inter-annual variability. Here, we have dynamically downscaled 30 years of the Climate Forecast System Reanalysis (CFSR) over these islands at 3-km horizontal resolution. The model output is found to agree well with the station and radiosonde data at the Port-aux-Français station, the only location in the islands for which observational data is available. An analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Food web dynamics significantly correlated with summer environmental trends and this is consistent with other studies showing strong summer environmental trends (Lovenduski and Gruber, 2005;Swart and Fyfe, 2012;Panassa et al, 2018;Fonseca and Martín-Torres, 2019;Meredith et al, 2019). Stronger correlations during summer between our model output and environmental data could be a result of the trends used to calibrate the model.…”
Section: Environmental Drivers Of Food Web Dynamicssupporting
confidence: 91%
“…Food web dynamics significantly correlated with summer environmental trends and this is consistent with other studies showing strong summer environmental trends (Lovenduski and Gruber, 2005;Swart and Fyfe, 2012;Panassa et al, 2018;Fonseca and Martín-Torres, 2019;Meredith et al, 2019). Stronger correlations during summer between our model output and environmental data could be a result of the trends used to calibrate the model.…”
Section: Environmental Drivers Of Food Web Dynamicssupporting
confidence: 91%
“…Predecessors have achieved good results in using WRF model to carry out research (Fonseca and Martín-Torres 2019), so this paper also adopt WRF model to simulate. By comparing the typhoon centre position and typhoon intensity of the WRF model with the actual CMA typhoon data at each time point, we found that the simulation results match well with the actual time point of intensity change and maximum wind speed (12:00 UTC on October 27 th ).…”
Section: Methods and Modementioning
confidence: 99%